Ethnopedagogy of the osing tribe folk song: exploration and formation of biology learning character - Hariyadi, Slamet; Tamalene, M. Nasir; Hariyono, Aekanu (Biosfer: Jurnal Pendidikan Biologi, 2019)
Exploration of ethnopedagogical values of the Osing tribe is essential to uncover the values of biological characters because the Osing tribe 3closely related to the application of biological science, for example, in utilizing plants for traditional ceremonial activities or as medicinal plants. This study aims to explore the character values contained in the folk song of the Osing Banyuwangi tribe, related to the formation of attitudes or characters needed in studying biology. The study was conducted using a survey method using structured interview techniques, semi-structured interviews, and in-depth interviews of 15 informants selected using Purposive Sampling and snowball sampling techniques. Data analysis consists of 3 stages: data reduction, data presentation, and making conclusions. The results of the study mentioned that the ethno-pedagogical values are found in “Tetak-tetak” and “Nggolek Ilmu” folk song of Fatrah-Abal. These two songs express explicit and implicit values of biological characters. The tetak-tetak and nggolek ilmu folk song became a community media in instilling the attitude or character values needed in studying biology at pre-school age. These values ​​will be further developed in learning biology in schools, which are carried out in an integrated manner in affective aspect.